2015
DOI: 10.5539/ijms.v7n1p138
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Internal Marketing on Organizational Citizenship Behavior an Applicable Study on the University of Jordan Employees

Abstract: A tremendous shifting of businesses at the present time forced organizations to live in a dynamic, ambiguous, and changeable environment. Due to these challenges, organizations need to apply the new marketing orientation that enhance businesses; and improve their businesses permanently to keep their competitive excellence. One of the main important factors to consider is by attracting new customers and maintaining healthy long-term relationship with them. This cannot be accomplished without improving the organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…In most of the empirical studies conducted in various service sectors, it was seen that there was a positive and significant relationship between internal marketing and OCB (Alper Ay, 2018;Alshurideh, Alhadid and Barween, 2015;Chang, Tseng and Chen, 2012;Seyed Javadin, Rayej, Yazdani, Estiri and Aghamiri, 2012;Yildiz, 2016b). Our study on employees in the sports industry has shown that, similar to other research, internal marketing affects OCB significantly and positively.…”
Section: Discussionsupporting
confidence: 83%
“…In most of the empirical studies conducted in various service sectors, it was seen that there was a positive and significant relationship between internal marketing and OCB (Alper Ay, 2018;Alshurideh, Alhadid and Barween, 2015;Chang, Tseng and Chen, 2012;Seyed Javadin, Rayej, Yazdani, Estiri and Aghamiri, 2012;Yildiz, 2016b). Our study on employees in the sports industry has shown that, similar to other research, internal marketing affects OCB significantly and positively.…”
Section: Discussionsupporting
confidence: 83%
“…This result shows similarities with the other researches carried out in higher educational institutions. In their researches, Alshurideh, Alhadid, and Barween [1] and Carlos and Rodrigues [9] found that IM applications have positive and significant effects on academic staff's OCBs.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this framework, a considerable number of studies have investigated the effect of internal marketing on employee job satisfaction and employee behaviors (Altarifi, ). In the latter category, organizational citizenship behavior has received the most attention of internal marketing researchers (Alshurideh, Alhadid, & Barween, ; Awan et al., ; Awward, & Agti, ). Regrettably, while adaptive selling behavior, customer‐oriented selling behavior, and relational selling behavior have been suggested as the most effective approaches to establishing and nurturing long‐term relations with customers as well as yielding higher sales performance (Bayaa, Goedegebuure, & Jones, ), they have not been studied in relation to internal marketing.…”
Section: Introductionmentioning
confidence: 99%